Income Redistribution and Social Policy: A Set of Studies - Bronfenbrenner, M.; Peacock, Alan T. (The Review of Economics and Statistics, 1955)
This set of studies investigates the nature and magnitude of the redistribution of income throughout the world. Each of the distinguished authors addresses questions as complex as how governmental social policies effected the redistribution of income and what were the consequences.